Two- to Six-year Assessment of Survivorship and Patient-Reported Outcomes in Rotating Hinge Knee Prostheses With Porous Tibial Cone Augmentation - Matthew Van Engen, MD; Taylor Den Hartog, MD; Natalie Glass, PhD; Nicolas Noiseux, MD (Arthroplasty Today)
Background: Rotating hinge knee (RHK) implants are a highly constrained prosthesis designed for knee arthroplasty cases involving significant knee instability. RHK systems are often augmented with metaphyseal tibial cones (MTCs). This study investigated structural stability and patient-reported outcomes (PROs) of RHKs with MTC augmentation. Methods: All RHKs utilizing MTC were identified at a single institution from 2016 to 2021. Patients returned for radiographic evaluation, physical exam, and PROs. A total of 84 knees (80 patients) were identified, 44 cases (43 patients) followed up greater than 2 years after their RHK procedure. A cumulative incidence function curve was constructed, and failure was defined as a subsequent revision. PROs included Knee Injury Osteoarthritis Outcome Score for Joint Replacement and Patient-Reported Outcome Measurement Information System (PROMIS)−10. Patient Acceptable Symptom State and postoperative rating of improvement scores were collected. Results: Cumulative incidence function all-cause failure (N = 84) was 18% at 2.8 years. The diagnoses for failed cases were infection (6 cases), mechanical failure (1 case), and persistent pain (1 case). The mechanical failure was due to loosening of the femoral component requiring femoral only revision. No follow-up cases (N = 44) demonstrated evidence of loosening at the MTC–RHK interface, median follow-up time of 3.82 years. Mean range-of-motion was 0°-120°. Mean PROs were 61.4 for Knee Injury Osteoarthritis Outcome Score for Joint Replacement, 41.2 for PROMIS Mental Health, and 47.9 for PROMIS Physical Health. Patient Acceptable Symptom State was attained by 68% of follow-up cases and 75% reported moderate or better improvement in their quality of life after their RHK. Conclusions: RHK with MTC augmentation did not reveal any cases of loosening of the MTC with only 1 case of femoral loosening. Level of Evidence: III.